Responses of the antennal bimodal hygroreceptor neurons to innocuous and noxious high temperatures in the carabid beetle, Pterostichus oblongopunctatus. (October 2015) - Nurme, Karin; Merivee, Enno; Must, Anne; Sibul, Ivar; Muzzi, Maurizio; Di Giulio, Andrea; Williams, Ingrid; Tooming, Ene
Graphical abstract: Highlights: The antennal dry and moist neurons are sensitive to air humidity and temperature. Noxious high temperatures evoked spike bursts in the hygroreceptor neurons. Burstiness of the spike trains of hygroreceptor neurons is temperature dependent. Spike bursts of hygroreceptor neuron might be involved in thermoregulation behaviour. Abstract: Electrophysiological responses of thermo- and hygroreceptor neurons from antennal dome-shaped sensilla of the carabid beetle Pterostichus oblongopunctatus to different levels of steady temperature ranging from 20 to 35 °C and rapid step-changes in it were measured and analysed at both constant relative and absolute ambient air humidity conditions. It appeared that both hygroreceptor neurons respond to temperature which means that they are bimodal. For the first time in arthropods, the ability of antennal dry and moist neurons to produce high temperature induced spike bursts is documented. Burstiness of the spike trains is temperature dependent and increases with temperature increase. Threshold temperatures at which the two neurons switch from regular spiking to spike bursting are lower compared to that of the cold neuron, differ and approximately coincide with the upper limit of preferred temperatures of the species. We emphasise that, in contrast to various sensory systems studied, the hygroreceptor neurons of P. oblongopunctatus have stable and continuous burst trains, no temporal information is encoded in the timing of the bursts. We hypothesise that temperature dependent spike bursts produced by the antennal thermo- and hygroreceptor neurons may be responsible for detection of noxious high temperatures important in behavioural thermoregulation of carabid beetles.